1, 2, 5‐Triphenylpyrrole Derivatives with Dual Intense Photoluminescence in Both Solution and the Solid State: Solvatochromism and Polymorphic Luminescence Properties. Issue 2 (13th December 2018) - Li, Yuanyuan; Lei, Yunxiang; Dong, Lichao; Zhang, Longlong; Zhi, Junge; Shi, Jianbing; Tong, Bin; Dong, Yuping
Abstract: Five organic luminophores, 1, 2, 5‐triphenylpyrrole (TPP) derivatives3 a –e bearing electron‐withdrawing or electron‐donating groups, have been synthesized by Pd‐catalyzed Suzuki coupling of 1‐phenyl‐2, 5‐di(4′‐bromophenyl)pyrrole and para ‐substituted phenylboronic acid derivatives. They possess good thermal stabilities with high decomposition temperatures above 310 °C. Investigation of the photophysical properties of the luminogens3 a –e indicated that they exhibited dual intense photoluminescence in both solution and the solid state due to their twisted conformations, and their fluorescence quantum yields ( Φ F ) were determined as 68.7–94.9 % in THF solution and 19.1–52.0 % in solid powder form. Compounds3 a –c bearing electron‐accepting groups exhibited remarkable solvatochromism with large Stokes shifts, attributable to their D‐π‐A structure and intramolecular charge‐transfer effect. In particular, 3 a, bearing aldehyde groups, displayed an obvious red‐shift of the emission band from 445 to 564 nm with increasing solvent polarity. However, no obvious solvatochromic behavior was observed for compounds3 d, e bearing electron‐donating groups. The luminophore3 a exhibited polymorphic luminescence properties and crystallization‐induced emission enhancement. Abstract : Shining bright : 1, 2, 5‐Triphenylpyrrole derivatives bearing electron‐withdrawing or electron‐donating groups display dual intense photoluminescence both in solution and in the solid state. An electron‐accepting substituent causes them to exhibit remarkable solvatochromism with large Stokes shifts. The congener bearing −CHO groups exhibits CIEE features and polymorphic luminescence properties.